Analisis Perilaku Sosial Masyarakat Perkotaan dalam Pembelian Merchandise Pada Kalangan Remaja Kpop di Kota Medan - Hidayati, Syafitri; Harahap, Suheri (Jurnal Noken: Ilmu-Ilmu Sosial, 2024)
In today's modern era, social media is very influential in everyday life, especially in encouraging the purchase of goods online, as is done by teenagers who like Kpop who are very fond of buying Kpop merchandise. The method used in this research is qualitative research with a phenomenological approach. This data collection technique uses interview and observation techniques. The aim of the research is to analyze the social behavior of urban communities in purchasing merchandise among kpop teenagers, especially UINSU Medan students. The results of this research show that purchases of kpop merchandise among students are influenced by their own friends and the influence of social media from the Tiktok and Ig applications. Research to find out how students consume in purchasing merchandise in the city of Medan